2014
DOI: 10.1186/1471-2458-14-1237
|View full text |Cite
|
Sign up to set email alerts
|

Low control beliefs in relation to school dropout and poor health: findings from the SIODO case–control study

Abstract: BackgroundThere is cumulating evidence that health is compromised through adverse socioeconomic conditions negatively affecting how people think, feel, and behave. Low control beliefs might be a key mechanism. The reversed possibility that low control beliefs might set people on a pathway towards adverse socioeconomic and health-related outcomes is much less examined.MethodsA case–control design was used, consisting of 330 cases who dropped out of school in the 2010–2011 school year and 330 controls who still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Studies performed in a non-integrated diabetes care setting, found that context-related characteristics, such as socio-economic status and social network, are associated with measures of diabetes control and are likely to be strong predictors of diabetes control (Jotkowitz et al, 2006;Nam et al, 2011). Person-related characteristics, such as low mastery and low self-efficacy, have been related to negative health outcomes (Bosma et al, 2014;Elissen et al, 2017). Traditionally, researchers and care providers have looked at diabetes from a mostly biomedical viewpoint, which might explain the relatively scarce collection of context-and person-related characteristics in routinely collected individual patient data (Hasnain-Wynia and Baker, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in a non-integrated diabetes care setting, found that context-related characteristics, such as socio-economic status and social network, are associated with measures of diabetes control and are likely to be strong predictors of diabetes control (Jotkowitz et al, 2006;Nam et al, 2011). Person-related characteristics, such as low mastery and low self-efficacy, have been related to negative health outcomes (Bosma et al, 2014;Elissen et al, 2017). Traditionally, researchers and care providers have looked at diabetes from a mostly biomedical viewpoint, which might explain the relatively scarce collection of context-and person-related characteristics in routinely collected individual patient data (Hasnain-Wynia and Baker, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parental attention has to be shared which increases self-dependence, but can also give competition which makes children more defensible. In our study, self-efficacy, which stimulates the student’s drive and thus school attendance [ 40 ], is associated with less school dropout [ 11 ]. This suggests that increasing self-efficacy at an early age may help to prevent school dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors that influence the process of early school leaving are already identified [ 8 ] and can be divided in student-related (e.g. overall poor health in childhood and adolescence [ 3 ], externalizing and internalizing behavior [ 9 , 10 ], life-style, personality [ 3 , 11 , 12 ], sex differences and gender beliefs [ 13 ], family-related (e.g. living in a single-parent family[ 14 ]) and school-related factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings thus do not help in better explaining socioeconomic differences in health care use, nor do they help in envisaging different types of interventions aimed at tackling these differences. Future studies should try to avoid our study’s drawbacks and evaluate how also other third factors, such as control beliefs (Bosma et al 2014 ) and intellectual abilities (Batty et al 2006 ; Mackenbach 2005 ), might be driving forces in the aetiology of socioeconomic health differences.…”
Section: Discussionmentioning
confidence: 99%